2007
DOI: 10.1111/j.1600-0404.2007.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of genetic variability in the ?-amyloid production, aggregation and degradation metabolic pathways and the risk of Alzheimer?s disease

Abstract: The overall impact on AD risk of the genes for which meta-analyses are now available is rather limited. Additional meta-analyses of other different genes encoding for A beta production, aggregation and degradation mediators might help in determining the risk profile for AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 87 publications
(196 reference statements)
1
13
0
Order By: Relevance
“…The distribution of genotypes for the two polymorphisms did not diverge from the Hardy-Weinberg equilibrium ( Table 2). The frequencies of the BLMH genotypes in the all groups were similar to those previously reported in the literature [18]. There were no significant differences in APOE genotypes or allele distributions between groups ( Table 2); however, the genotype 3/3 was most frequent for all subjects (61.1%).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The distribution of genotypes for the two polymorphisms did not diverge from the Hardy-Weinberg equilibrium ( Table 2). The frequencies of the BLMH genotypes in the all groups were similar to those previously reported in the literature [18]. There were no significant differences in APOE genotypes or allele distributions between groups ( Table 2); however, the genotype 3/3 was most frequent for all subjects (61.1%).…”
Section: Resultssupporting
confidence: 87%
“…Previous studies investigating BLMH 1450 G > A in AD and control subjects have found that subjects with the G/G alleles and without APOE allele 4 had four times greater likelihood to have AD [23][24][25]. However, this association between BLMH genotypes and AD was not found by other researchers [18,[26][27][28]. The relationship between BLMH expression and Val443Ill isoforms with amount of patients bigger than our study, it still is an alternative for another researchinasmuch as the 1450 G > A covers the BH's active and it can have an influence about the disease.…”
Section: Discussionmentioning
confidence: 79%
“…In addition a meta-analysis of the available data does not support a link between genetic variations in CYP46A1 and the risk of AD (Llorca et al, 2008).…”
Section: Introductionmentioning
confidence: 86%
“…A significant association between the rs638405 GG genotype and AD was noted [6]. This study has been replicated by several research teams, although some found contrasting results [7]. …”
Section: Introductionmentioning
confidence: 62%